2004
DOI: 10.1111/j.1525-1594.2004.00017.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Vertical Orientation and Stability of Acetabular Component in the Dysplastic Hip Simulated by Nonlinear Three‐dimensional Finite Element Method

Abstract: In acetabular dysplasia, more vertical orientation of the acetabular component is often used to minimize the superolateral bone grafting. This study was designed to determine the effects of vertical orientation of the cup on the stability and polyethylene wear of the acetabular component in uncemented total hip arthroplasty (THA). Three-dimensional finite element models of the hemipelvis with dysplastic acetabulum were developed. Metal-backed hemispherical cups were placed in the true acetabulum with abduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
1
19
0
1
Order By: Relevance
“…The lack of difference in linear PE wear rate and variance between the NHC and HHC groups and the wide distribution of PE wear values in both groups are in accordance with the results of studies that found not only the hip center is responsible for PE wear in a hip arthroplasty but also numerous other factors, such as cup inclination, articulating surfaces, femoral head size, and patient age or body weight [16,17,20,23,24,38].…”
Section: Discussionsupporting
confidence: 74%
“…The lack of difference in linear PE wear rate and variance between the NHC and HHC groups and the wide distribution of PE wear values in both groups are in accordance with the results of studies that found not only the hip center is responsible for PE wear in a hip arthroplasty but also numerous other factors, such as cup inclination, articulating surfaces, femoral head size, and patient age or body weight [16,17,20,23,24,38].…”
Section: Discussionsupporting
confidence: 74%
“…A diametral clearance of 0.1mm (Kurtz et al 2000;Oki et al 2004) and contact elements were simulated and used at the interface between the femoral head implant and the acetabular component. This contact was assumed to be frictionless (Dalstra 1993).…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Contact elements were used at the subchondral bone and cement mantle interface to represent the mechanical interlock between the bone and the cement [40]. A diametral clearance of 0.1 mm [41,42] was modelled and frictionless contact elements [30] were used at the interface between the femoral head implant and the acetabular component. Our sensitivity analyses of the effect of frictional moments on the stress distribution in the reconstructed hemi-pelves showed only a small relative change of 2-3% in the tensile stress level in the cement mantle.…”
Section: Boundary Conditionsmentioning
confidence: 99%